Acquisition of non-native vowel duration contrasts through classroom education: Perception and production affected differently - Saloranta Antti; Heikkola Leena Maria (John Benjamins Publishing Company, 2022)
In quantity languages, the durations of segments affect the meanings of words. This can present problems for second language (L2) learners who do not already have this feature in their native language. This study examines the effects of an intensive, four-week language course with a communicative focus on the perception and production of non-native vowel duration contrasts. A total of 68 students of Finnish, divided into speakers of quantity or non-quantity languages, took part in identification and production tests before and after taking part in the course. The course produced a significant improvement on identification, but not production. Furthermore, a slight advantage was found for speakers of quantity languages in the identification task. Comparison to native control groups revealed significant differences between groups in both tasks. The results are discussed in relation to the interaction of perception and production, L2 learning models and relevance to L2 teaching.